Chronic Toxicity Of High Molecular Weight Polynuclear Aromatic Hydrocarbon- Pyrene On Freshwater Cyanobacterium Anabaena Fertlissima Rao - Patel, Jignasha G; Kumar, JI Nirmal; Kumar, Rita N; Khan, Shamiyan R (International Journal of Environment, 2013)
The aim of this work was to determine the consequences of Polynuclear aromatic hydrocarbon – Pyrene in response to growth, pigments and metabolic study on Anabaena fertilissima Rao. Test organisms were treated at different doses and encountered LC50 (Lethal concentration at which 50% growth reduction occur) concentration separately at 1.5 mg/l, 3.0 mg/l and 6.0 mg/l respectively for Anabaena fertilissima Rao. The influence of Pyrene on growth, pigments, release of metabolites such as carbohydrates, protein, amino acid, phenols was carried out. The test doses caused a concentration dependent decrease in pigments like carotenoids and phycobilliproteins and showed more sensitivity to pyrene. Depletion of carbohydrate by 13% to 81% and proteins by 47% to 93% was encountered with rise in pyrene concentrations after 16th day of exposure. However, phenols were found to rise by 27% to 50% with increased pyrene concentrations on the contrary, amino acids were reported to decline by 79% to 92%. This study therefore suggests high molecular weight pyrene that decreases in metabolite content and enzyme activity can be used as a signal of PAHs toxicity in cyanobacteria. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 175-183 DOI: http://dx.doi.org/10.3126/ije.v2i1.9220